HIV post-exposure prophylaxis provided at an urban paediatric emergency department to female adolescents after sexual assault. Issue 4 (18th June 2004) - Merchant, R C; Keshavarz, R; Low, C
Abstract : Background: In 1998, the New York State Department of Health released guidelines governing the provision of HIV post-exposure prophylaxis (HIV PEP) after adolescent and adult sexual assault. This study sought to examine the extent of HIV PEP provision in a New York City paediatric emergency department (ED) after the release of these guidelines. Methods: Using logs of the sexual assault and violence intervention advocacy programme, the authors identified patients who had been evaluated for sexual assault in the hospital's paediatric ED from January 1999 to December 2000. These patients' medical records were reviewed retrospectively for details of their sexual assault and the medical treatment they received in the paediatric ED. Results: Of 25 patients identified from the hospital's affiliated sexual assault and violence intervention advocacy programme logs, 14 female adolescents had received HIV PEP. Each patient had suffered forced vaginal intercourse. Sixty four per cent of the survivors knew their assailant, but none knew his HIV status. No patients received HIV PEP within the optimal one hour prescription time, but no patient presented within the one hour window. Eighty six per cent presented >12 hours and 42% >24 hours after assault. HIV PEP was ordered an average of 218 minutes after the patient presented to the ED. Patients received drugs an average of 58 minutes after they were ordered. All but one patient received a three drug regimen. Conclusions: This study advocates improved efforts to expedite HIV PEP provision in the ED, such as educating ED practitioners on its proper use, and making HIV PEP drugs available for direct dispense from the ED.